Return mobilities of Zanzibar exiles in the 2010s and the reshaping of a common world - (:unkn) unknown (My University, 2024)
Panel 6 : Mobilities & colonial times.Several factors contribute to the return of post-revolutionary exiles to Zanzibar in the 2010s (exile retirement, post-Maridhiano political evolution, tourism development). In fact, returns actually take the form of multi-year back and forth movements (va-et-vient) between the Gulf, Europe, northern America and Zanzibar, as well as more complex circulations between the three main poles that structure post-revolution zanzibar diaspora.Throughout the 2010s, the city of Zanzibar has become a pivot of these mobilities. Urban places have been reappropriated contributing to the rerooting and reconnexion of zanzibaris dispersed in these regions of the worlds and residents.This article aims at informing the spatial, social and symbolic dimensions of this encounter from the beginning of the 2010's and the role of urban places and sociabilities in this process by emphasizing on Zanzibaris exiles from Oman, Dubai, UK, Danemark and Germany. It then seeks to analyze how returnees mobilities and reconnexions contribute to reshaping of a common world among dispersed zanzibaris between the Gulf countries, northern Europe and east-african cities, links with/and functions of/ exile countries in their lives through the specific experiences and challenges that characterize the itineraries of this generation. Finally, it hope giving elements of understanding on how return mobilities contribute repositioning the self in a common world that can play the function of a home during the last period of their lives, renewing identity affiliations (at different levels : homeland, emigration states, diaspora), reinterpretating of the past and planning the future.
Keywords: African Research